Student Teachers Perception Towards Teaching Practicum Programme - Normah, Yusof; Akmah, Yusof; Azahari, Md Ali; Che Mohd Nazrin, Che Mohd Yusoff (2014)
One of the requirements to qualify as a teacher is to undergo a teaching practicum during which one gains teaching experience. This practicum is considered as the most significant way in helping student teachers to become effective classroom teachers. This study investigates UniSZA student teachers perception towards teaching practicum and the challenges encountered by them. 45 Diploma in Teaching of English (TESL) Semester 5 students at the Faculty of Languages and Linguistics (FLL), Universiti Sultan Zainal Abidin (UniSZA) were chosen as respondents. The research employed qualitative methodology with questionnaire administered to examine the respondent’s answer for every question asked. The findings indicated that the student teachers have different perception and expectation regarding teaching practicum but most of them looked forward to it. The result of this study also highlighted two prominent challenges encountered by the student teachers that were to adapt with the school environment and the classroom management. Findings of this study would provide a deeper understanding on the Teaching Practicum organized by the Faculty of Languages and Communication.